From voice to the hands: towards a piano method - Tsihelashvili, Olga (My University, 2009)
My work revolves around Alexander Yakovlev’s vocal method which originates in the tradition of organic singing established in Russia by Glinka in the mid nineteenth century, and developed by the legendary Russian bass Fyodor Chalyapin. My approach to piano technique and performance formed as a direct result of Yakovlev’s principles and his vocal method, serves as the origin in my search for piano mastery. Being taught organic singing simultaneously with my piano studies by Yakovlev’s successor Natalia Pirozerskaya in my early childhood, I did not at that point see the full benefit of this approach for my piano skills. It was only after twelve years of trial and error in seeking to realise my inner expressive and virtuoso potential at the piano, that I understood the infinite value of Pirozerskaya’s teaching method and began to analyse the effect of organic singing on my pianistic process. Pirozerskaya grounds her research on the singing voice following Yakovlev’s concept of the vocal apparatus functioning as a sensory organ in relation to musical performance. Yakovlev developed a theory around this phenomenon which he labelled funzione d’attacco. This way, the singer’s inner artistic impulses cause a direct, natural motor response in his/her vocal organ, forming optimal corresponding movements which with training become automatic, almost reflexive. Pirozerskaya believes that because the vocal organ is an embodied instrument positioned close to the brain, organic vocal movements easily stimulate the brain, serving to alert and coordinate the motor-muscular responses of the entire body, and thus helping to form differentiated musical movements of the hands – the apparatus of the pianist. My research is focused on these phenomena in relation to piano playing. I am working towards systematising Pirozerskaya’s and my own further discoveries on how this unique vocalpiano method impacts on piano technique. Aiming to distinguish between the notions of a ‘good piano player’ and a ‘performing artist’, I am developing my proposed piano method of re-connecting the pianist with his inner artistic self. Combining my experience with relevant ideas of several renowned piano pedagogues from Frederick Chopin to the present, I propose an approach to piano playing which, I believe, has the capacity of maximising artistic expression in performance through developing a natural functional balance of pianistic movements inseparable from the pianist’s artistic aims
Keywords: paino method; voice; hands